(untitled) (Community Based Medical Journal, 2013)
This cross sectional descriptive study was performed by examining 30 (thirty) relatively fresh cerebellum of Bangladeshi cadaver of both sexes and samples were collected by using nonprobability sampling technique. Out of them 20 postmortem human cerebellum collected from Bangladeshi cadavers of both sexes (male 10 and female 10) age ranging from 5 to 60 years and 10 cerebellums from caesarian section of dead fetuses of both sexes (male 6 and female 4) age ranging from 34 wks to 41 wks. Specimen containing cerebellum was collected from dead bodies autopsied on different dates from April2009 to September2009 at the autopsy laboratory of department of Forensic Medicine and Gynaecology and Obstetrics Department of Mymensingh Medical College, Mymensingh. The collected sample was grouped in to three age groups like Group A (34 to 41 weeks of gestation), Group B (5 to 30 years) and Group C (31 to 60 years) and two sex groups (male and female). 10 cerebellums were studied from each age group for this histological study. Sections were processed following standard histological procedure and were stained with Hematoxylin and Eosin stain. Slides were examined under 15X40 magnification for counting the number of Purkinje cell. In this study, the mean difference of number of Purkinje cell between age Groups A&C was statistically highly significant (p<0.001) but difference between Groups A&B and B&C statistically was not significant. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14181 Community Based Medical Journal Vol.2(1) 2013 39-42